2013
DOI: 10.12720/jcm.8.12.845-854
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Power Control Techniques in Femtocell Networks

Abstract: Rapid increase in mobile data has raised the stakes on developing innovative new technologies and cellular topologies that can meet these demands in an energy efficient manner. One of the most interesting trends that will emerge from this cellular evolution is the femtocell networks. Femtocells are small, inexpensive, low power base stations that are generally consumer deployed, and are expected to significantly improve the coverage and capacity of the indoor users. Femtocell base stations (FBSs) have extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…The complexity of the centralized networks occurr because the process of computing at the base station is too much, which is related to the processing of all information from the environment and the users [16]. Therefore, the implementation of distributed systems that use only local information would be more realistic to be applied [17]. However, these two different schemes require feasibility test at the time before it will be implemented, as seen in Figure 3.…”
Section: Feasibility Of Power Control For Multi-channel Usermentioning
confidence: 99%
“…The complexity of the centralized networks occurr because the process of computing at the base station is too much, which is related to the processing of all information from the environment and the users [16]. Therefore, the implementation of distributed systems that use only local information would be more realistic to be applied [17]. However, these two different schemes require feasibility test at the time before it will be implemented, as seen in Figure 3.…”
Section: Feasibility Of Power Control For Multi-channel Usermentioning
confidence: 99%
“…The complexity of the centralized networks occurr because the process of computing at the base station is too much, which is related to the processing of all information from the environment and the users [16]. Therefore, the implementation of distributed systems that use only local information would be more realistic to be applied [17]. However, these two different schemes require feasibility test at the time before it will be implemented, as seen in…”
Section: Feasibility Of Power Control For Multi-channel Usermentioning
confidence: 99%
“…QoS improvement of edge users at each femtocell results in overall edge users performance gain at the network level. Authors in [15], concluded that the best way to achieve this with minimum complexity and signalling overhead between the network elements is through non-assisted self learning and adjusting methods. One of the latest research on this methodology has been done in [16] using stochastic learning algorithm, whereby femtocells independently learn and select CCs that result in minimum interference to the network.…”
Section: S a S Y S T E M Wo R K S A1 S Mar T E R S Is A1 S Mar T E R mentioning
confidence: 99%